The nematode assemblage as a tool for the assessment of marine ecological quality status: a case-study in the Central Adriatic Sea - SEMPRUCCI, F.; MORENO, M.; SBROCCA, S.; ROCCHI, M.; ALBERTELLI, G.; BALSAMO, M. (Mediterranean Marine Science, 2013)
Free-living nematodes are efficiently used as bio-indicators of anthropogenic disturbance in marine ecosystems. Among various criteria, functional traits may represent useful tools for monitoring environmental impact in coastal areas. A study of nematode assemblages was carried out in three locations of the Central Adriatic Sea (Italy), one at the mouth of the Foglia River (Baia Flaminia) and two enclosed in the Monte San Bartolo Natural Park (Monte Brisighella and Fiorenzuola di Focara). Taxonomic composition and the functional traits of the nematode assemblage revealed a possible influence of the organic load of the Foglia River. Biotic data, as well as environmental parameters, suggested a particularly negative impact of the river on the assemblage at Baia Flaminia. Here, the increasing impact of the river led to a rise in the relative abundance of r-strategist genera like Chromadora, Sabatieria and Viscosia. Poor ecological conditions were also present at Brisighella, where the river might exert its influence due to the presence of long shore currents. In contrast, the results revealed that the best ecological quality was at Fiorenzuola di Focara, where the impact of anthropogenic activities was generally irrelevant. This study documents how nematodes can be used as an early warning indicator with which to monitor the health quality of vulnerable littoral areas.